2021
DOI: 10.5005/jp-journals-10084-12173
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Assess the Prevalence and Contributing Factors of Abnormal Uterine Bleeding among Women Admitted in MGMCRI from January to December 2019

Abstract: Introduction: About 30% of women may have unexplained uterine bleeding at some stage in their lives. There are considerable costs to both the economy and the health sector, in addition to the direct effects on the woman and her family. After excessive bleeding has been established, the acronym PALM-COEIN is increasingly being used to classify the causes. Objectives: To assess the prevalence and to find out the contributing factors of abnormal uterine bleeding (AUB). Materials and methods: A retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Anxiety and depression frequently observed in women with AUB.It has been observed that from various study the women with AUB experienced the most common psychological symptoms such as depression and anxiety.AUB also associated with more negative course and more negative outcome. 14 Women with AUB (15.6%) had major depression, 18.8% of women had generalized anxiety disorder and 22.9% interfere with the quality of life and mood problems such as anxiety and depression also associated with abnormal uterine bleeding and AUB associated with more negative impact anxiety -depression comorbidity. 15…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and depression frequently observed in women with AUB.It has been observed that from various study the women with AUB experienced the most common psychological symptoms such as depression and anxiety.AUB also associated with more negative course and more negative outcome. 14 Women with AUB (15.6%) had major depression, 18.8% of women had generalized anxiety disorder and 22.9% interfere with the quality of life and mood problems such as anxiety and depression also associated with abnormal uterine bleeding and AUB associated with more negative impact anxiety -depression comorbidity. 15…”
Section: Introductionmentioning
confidence: 99%